Chinese Transnational Migration in the Age of Global Modernity : The Case of Oceania - Liu, Liangni Sally (London : Taylor and Francis, 2018)
"The term 'circulatory transnational migration' best describes the unconventional migratory route of many contemporary Chinese migrants--that is an unfinished set of circulatory movements that these migrants engage in between the homeland and various host countries. 'Return migration', 'step migration' to a third destination and the 'astronauting' strategy are all included within this circulatory migration movement wherein 'returning' to the country of origin does not always mean to settle back to the homeland permanently; while 'step migration' also does not necessarily mean to re-migrate to a third destination country for a permanent purpose. Liu takes a longitudinal perspective to study Chinese migrants' transnational movements and looks at their transnational migratory movements as a family matter and progressive and dynamic process, using New Zealand as a primary case study. She examines Chinese migrants' initial motives for immigrating to New Zealand; the driving forces behind their adoption of a transnational lifestyle which includes leaving New Zealand to return to China, moving to a third country--typically Australia - or commuting across borders; family-related considerations; inter-generational dynamics in transnational migration; as well as their future movement intentions. Liu also discusses Chinese migrants' conceptualisation of 'home', citizenship, identity, and sense of belonging to provide a deeper understanding of their transnational migratory experiences."--Provided by publisher.
chapter 1 Introduction -- r Liangni Sally Liu -- chapter 3 Re-grounding (3z(Btransnationalism(3y (Bin theories and practices /s Liangni Sally Liu -- chapter 4 Changing family strategies and onward movements / Liangni Sally Liu -- chapter 5 Conceptualisation of (3z(Bhome(3y(B, identity, sense of belonging, and citizenship /s Liangni Sally Liu -- r Liangni Sally Liu -- r
Keywords: Chinese -- Migrations; Transnationalism